Anthropometric characteristics of volleyball and waterpolo players - Papadopoulou, S. K.; Papadopoulou, S. D.; Patsanas, T.; Dalkiranis, A.; Papadopoulos, G. K.; Hassapidou, M. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was to compare the age and the anthropometric characteristics of male athletes of two different team sports (of which one is played in the court and the other in the water). Results: Volleyball athletes had significantly higher wrist circumference and body height in relation to water polo athletes (p<.05). This finding can be attributed to the fact that volleyball elite athletes prerequisite to have high height and great strength in wrist and fingers, due to the nature and the type of the sport. The higher wrist circumference might be caused by injuries and over training load that can provoke bones cartilages deformities specifically during adolescence. There is an apparent effect of the type of the sport on the anthropometric characteristics of the team sport athletes, which should be taken into account while selecting young athletes.